2014
DOI: 10.1007/s00280-014-2578-6
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of the selective ALK inhibitor alectinib in models of intracranial metastases

Abstract: We established intracranial tumor implantation models of EML4-ALK-positive NSCLC. Alectinib showed potent efficacy against intracranial EML4-ALK-positive tumor. These results demonstrated that alectinib might provide therapeutic opportunities for crizotinib-treated patients with brain metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
146
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(154 citation statements)
references
References 22 publications
7
146
0
1
Order By: Relevance
“…Based on these data, Japan was the first country to approve the use of alectinib. This agent is also effective in cases resistant to crizotinib, which is a first-generation ALK-TKI, including cases with metastasis to the central nervous system (6)(7)(8)(9). Based on these positive results, alectinib received breakthrough therapy designation by the FDA.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data, Japan was the first country to approve the use of alectinib. This agent is also effective in cases resistant to crizotinib, which is a first-generation ALK-TKI, including cases with metastasis to the central nervous system (6)(7)(8)(9). Based on these positive results, alectinib received breakthrough therapy designation by the FDA.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinically, alectinib produces high CNS-to-plasma ratios and impressive intracranial disease activity in animal models (14). In the NP28761 and NP28673 studies, brain metastases were present at study entry in approximately 60% of crizotinib-resistant patients (8,9).…”
mentioning
confidence: 99%
“…Therefore, drugs with increased CNS activity are urgently needed. Alectinib is a very promising agent in this setting, since a preclinical study showed that it is not a substrate of P-glycoprotein (P-gp), a key efflux transporter that may impair drug penetration through the blood-brain barrier [18]. Consistently, a pooled analysis of crizotinib-pretreated patients with CNS metastases showed that alectinib provides a CNS-ORR of 64% in individuals with measurable CNS disease (n = 50) [19].…”
mentioning
confidence: 58%